Readiness of Disability-Friendly Services in Religious Institutions: A Case Study of the Yogyakarta City Ministry of Religious Office - Fatimatuz Zahro Diah Putri Dani; Fauziah Khoiriyani; Dian Hafit Syaifullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article aims to analyze the availability of facilities for persons with disabilities as well as the challenges in implementing accessible spaces and facilities at the Yogyakarta City Office of the Ministry of Religious Affairs (Kankemenag of Yogyakarta City). This study used a qualitative approach by exploring the social situation related to providing disability-friendly public services in religious institutions. The collected data, both primary and secondary, were analyzed using Miles Huberman's analysis. Based on the observations, Kankemenag of Yogyakarta City provided adequate facilities for persons with disabilities. Some of the facilities available include toilets for the diffable (a person who is differently abled), visitor parking, special service counters, guiding blocks, downhill fields, and wheelchairs. The supporting factors of Kankemenag of Yogyakarta City can provide facilities for service users sourced from internal and external factors. The internal supporting factor found in the field is the commitment and mindset of the head from the Chief to the service officers. Meanwhile, the external factors supporting this case are more about the obligation to meet the requirements to achieve the xcellent Service title. The Ontario Human Rights Commission developed the barriers factor in providing facilities for those with special needs in public service, which consists of attitudinal, architectural, and informational barriers. The diverse scope of the study is strongly recommended to provide a broader picture of providing facilities for persons with disabilities in various places. This study is expected to improve public services in government agencies that are fair and equitable for all levels of society.